大學教師教學專業發展之個案研究－以 N 科技大學為例 A Case Study on Teaching Professional Development of University Faculty: Taking N University of Science and Technology as an Example - 張媛甯 Chang, Yuan-Ning (National Changhua University of Education, 2012)
本研究以大學校院教師教學專業發展為焦點，選擇近年來連續獲得教育部「教學卓越計畫」獎助經費的N 科技大學為研究對象，運用半結構式訪談與文件分析蒐集資料進行個案研究。研究結果顯示：N 科技大學教師教學專業發展在教學卓越計畫經費補助下推展更豐富的活動內容，並配合高等教育政策及學校教師評鑑制度；教學專業發展朝向多元化的教師自發性成長活動，包括教學優良教師經驗分享與課堂觀摩、微型教學、傳習制度與專業社群；影響教師教學專業發展的主要因素，除了教師對其職責的看法和教學專業發展的態度、需求與動機外，學校組織制度、氣氛與文化也是重要因素，而時間缺乏則是最大的阻礙因素。最後，本研究根據研究結論提出建議，作為個案學校及後續研究之參考。 This study analyzed teaching professional development of university faculty in N Science and Technology of University which had the honor to get subsidy fund of University Teaching Excellence Program in recent years, and used semi-structured interviews and document analysis as research methods. The study had following findings: 1. Due to fund of University Teaching Excellence Program, there were plentiful activities of faculty teaching professional development, which were tied in university policy and faculty evaluation system. 2. Teaching professional development aimed to spontaneous growth activities. 3. The main influential factors of teaching professional development included: (1) faculty's viewpoints of duties, (2) the attitudes, demands, and motives of teaching professional development, (3) the organizational system, climate and culture in N Science and Technology of University. 4. Time lack was the most impeding factor. Based on the findings, some suggestions were proposed for N Science and Technology of University and future studies.